2001
DOI: 10.1164/ajrccm.163.1.9912036
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Endothelial Cells in Patients with Septic Shock

Abstract: The vascular endothelium has a central role in the control of microvascular tone, and it has been proposed that vascular endothelial damage occurs in septic shock, producing multiorgan failure. We have developed a method of detecting circulating endothelial cells (EC) that provides direct evidence of EC shedding in human sepsis. Human umbilical vein endothelial cells (HUVEC) were seeded in whole blood and recovered by isopycnic centrifugation to validate the technique. Blood samples were subsequently taken fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
1
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(155 citation statements)
references
References 28 publications
5
142
1
7
Order By: Relevance
“…In this study, CEC counts markedly increased in patients with sepsis (850% increase) and septic shock (1580%), when compared with healthy controls, suggesting that endothelial damage precedes the clinical development of organ failure [1]. In contrast to our study, which uses the more established immunobead method of quantifying CECs, Mutunga et al [5] identified CECs by using immunohistochemistry with a polyclonal antihuman VWF. Whilst our experimental LPS endotoxemia model does provide valuable insights into host responses to gram-negative infection, it does not necessarily equate to clinical septicemia.…”
contrasting
confidence: 69%
“…In this study, CEC counts markedly increased in patients with sepsis (850% increase) and septic shock (1580%), when compared with healthy controls, suggesting that endothelial damage precedes the clinical development of organ failure [1]. In contrast to our study, which uses the more established immunobead method of quantifying CECs, Mutunga et al [5] identified CECs by using immunohistochemistry with a polyclonal antihuman VWF. Whilst our experimental LPS endotoxemia model does provide valuable insights into host responses to gram-negative infection, it does not necessarily equate to clinical septicemia.…”
contrasting
confidence: 69%
“…Sickle cell disease is a vascular disease that causes tissue ischemia and exaggerated endothelial turnover, both of which are characterized by evident endothelial injury and regeneration [34]. In different patient groups, the number of ECs/mL of peripheral blood may vary between zero and 1,500; most studies found 1 to 100 circulating ECs/mL in healthy people [34][35][36][37][38][39][40]. We found much higher numbers of circulating ECs in both sickle cell patients and controls, probably due to methodological differences in sample preparation and cell quantification.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mature vascular endothelial cells in the circulation may be due to a variety of factors including traumatic injury, which causes them to slough off and carried away in the circulation (14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%